2007
DOI: 10.1038/sj.eye.6702716
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening tight junctions of retinal microvascular endothelial cells by pericytes under normoxia and hypoxia involving angiopoietin-1 signal way

Abstract: Purpose To determine the effects of pericytes and angiopoietin-1 on the expression of occludin and zonula occludens-1 (ZO-1) in retinal endothelial cells (ECs) under both normoxic and hypoxic conditions. Methods Rat primary retinal microvascular ECs were cultured under normoxia or hypoxia in either absence or presence of pericytes conditioned medium (PCM). PCM was pretreated with or without angiopoietin-1 neutralizing antibody. Immuofluorescent staining, Western blot and RT-PCR were used to detect the alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…The in vitro BBB model has revealed that pericytes are required to maintain BBB function (Hori et al 2004;Dohgu et al 2005;Parkinson and Hacking 2005;Hartmann et al 2007;Nakagawa et al 2007;Kim et al 2008;Zozulya et al 2008;Cardoso et al 2010). Close contact between pericytes and endothelial cells is essential Edelman et al (2006) Production of extracellular matrices Hartmann et al (2007) Regulation of endothelial tight junction proteins Kim et al (2009) and Nakagawa et al (2009) Pericytes strengthen barrier function by upregulating tight junction proteins via angiopoietin-1 (Hori et al 2004;Wang et al 2007;Kim et al 2008) and TGFb-1 (Dohgu et al 2005;Takata et al 2007) Regulation of endothelial transport systems Takata et al (2007) Regulation of endothelial MMP Virgintino et al (2007) and Zozulya et al (2008) Expression of tight junction proteins and barrier-related transporters in the pericytes Bendayan et al (2006) and Shimizu et al (2008) Cell Mol Neurobiol (2011 for barrier functions. In a triple coculture model, in which endothelial cells and pericytes were cultured on both sides of the filter membrane and astrocytes at the bottom of the culture dish, pericytes were necessary to maintain higher electrical resistance and lower permeability ).…”
Section: Mechanisms Of Bbb Regulationmentioning
confidence: 99%
“…The in vitro BBB model has revealed that pericytes are required to maintain BBB function (Hori et al 2004;Dohgu et al 2005;Parkinson and Hacking 2005;Hartmann et al 2007;Nakagawa et al 2007;Kim et al 2008;Zozulya et al 2008;Cardoso et al 2010). Close contact between pericytes and endothelial cells is essential Edelman et al (2006) Production of extracellular matrices Hartmann et al (2007) Regulation of endothelial tight junction proteins Kim et al (2009) and Nakagawa et al (2009) Pericytes strengthen barrier function by upregulating tight junction proteins via angiopoietin-1 (Hori et al 2004;Wang et al 2007;Kim et al 2008) and TGFb-1 (Dohgu et al 2005;Takata et al 2007) Regulation of endothelial transport systems Takata et al (2007) Regulation of endothelial MMP Virgintino et al (2007) and Zozulya et al (2008) Expression of tight junction proteins and barrier-related transporters in the pericytes Bendayan et al (2006) and Shimizu et al (2008) Cell Mol Neurobiol (2011 for barrier functions. In a triple coculture model, in which endothelial cells and pericytes were cultured on both sides of the filter membrane and astrocytes at the bottom of the culture dish, pericytes were necessary to maintain higher electrical resistance and lower permeability ).…”
Section: Mechanisms Of Bbb Regulationmentioning
confidence: 99%
“…It has angiogenic actions that are distinct from those of vascular endothelial growth factor and are mediated via a tyrosine kinase receptor expressed almost exclusively on endothelial cells. 44,45 Angiopoietin 1 also has anti-inflammatory properties, suppressing the expression of adhesion molecules and blocking vascular permeability through vascular endothelial growth factor inhibition and strengthening of endothelial tight junctions. 46 FLT1 is a tyrosine kinase receptor, which is expressed on the surface of retinal vascular endothelial cells and mediates the biological effects of vascular endothelial growth factor.…”
Section: Commentmentioning
confidence: 99%
“…Hyperglycemic exacerbation of ischemic myocardial injury is strongly associated with high glucose-induced endothelial dysfunction [2] . Studies have also shown that Ang-1 has a protective effect on endothelial cells injured by hypoxia [3] , arsenite toxicity [4,5] . However, few published data are available on the effects of Ang-1 on cardiac microvascular endothelium cultured under hyperglycemic conditions.…”
Section: Introductionmentioning
confidence: 99%